Resident and Staff Time and Activity Allocation in a Juvenile Justice Facility. Issue 2 (3rd April 2022) - Luna, Odessa; Anderson, Ashley A.; Rapp, John T.
ABSTRACT: Adolescents in juvenile justice facilities often lack critical social, academic, and vocational skills, which may limit their academic and employment opportunities following their release. One time period during which adjudicated adolescents can practice these critical skills with other residents and staff might be during leisure periods in their dorms. However, it is unclear (a) what activities are available for residents during leisure periods and (b) the extent to which staff members engage with residents during these activities. The purpose of the current study was to directly assess how residents and staff members in four dorms in a juvenile justice facility, which included a well-functioning comparison dormitory, allocated their time across available activities during indoor and outdoor leisure periods. Results indicated a lack of skill building activities available to residents across three of the four dorms, with residents often allocating their time to activities (e.g., television and video games) which might not promote pivotal life skills. The practical implications of these findings, as well as future directions for juvenile justice facilities and researchers, are briefly discussed.